The Impact of Student Entreprenurship Development Program on Student Entreprenurial Interest - Aji Priambodo (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
The Indonesian government is currently making efforts to strengthen the economy by fostering entrepreneurial human resources through an entrepreneurship development program in universities. The main objective of this research is to determine the role of the student entrepreneurship development program (Program Pembinaan Wirausaha Mahasiswa/P2MW) and entrepreneurship courses on the campus ecosystem and entrepreneurial interest of students at the Institut Teknologi dan Bisnis Muhammadiyah Purbalingga. To achieve this objective, an empirical research approach was used, employing a survey method with a 5-point Likert scale to collect data. This study used quantitative insight and structural equation modeling (SEM) to test seven hypotheses regarding the relationships among P2MW, campus ecosystem, entrepreneurship courses, and entrepreneurial interest. The findings of this research indicate that P2MW, campus ecosystem, and entrepreneurship courses have a positive and significant influence, both simultaneously and partially, on the entrepreneurial interest of students at the Institut Teknologi dan Bisnis Muhammadiyah Purbalingga.